Wave Reflection and Ventriculo-Arterial Coupling in Bicuspid Aortic Valve Patients With Repaired Aortic Coarctation - Milano, Elena Giulia; Neumann, Sandra; Sophocleous, Froso; Pontecorboli, Giulia; Curtis, Stephanie L.; Bedair, Radwa; Caputo, Massimo; Luciani, Giovanni Battista; Bucciarelli-Ducci, Chiara; Biglino, Giovanni (Frontiers in Pediatrics, 2022)
Background: Ventriculo-arterial (VA) coupling in bicuspid aortic valve (BAV) patients can be affected by the global aortopathy characterising BAV disease and the presence of concomitant congenital lesions such as aortic coarctation (COA). This study aimed to isolate the COA variable and use cardiovascular magnetic resonance (CMR) imaging to perform wave intensity analysis non-invasively to shed light on VA coupling changes in BAV. The primary hypothesis was that BAV patients with COA exhibit unfavourable VA coupling and the secondary hypothesis was that BAV patients with COA exhibit increased wave speed as a marker of reduced aortic distensibility despite successful surgical correction. Methods: Patients were retrospectively identified from a CMR database and divided into two groups: isolated BAV and BAV associated with repaired COA. Aortic and ventricular dimensions, global longitudinal strain (GLS) and ascending aortic flow data and area were collected and used to derive wave intensity from CMR data. Main variables for the analysis included all wave magnitudes (forward compression/expansion waves, FCW and FEW, and reflected backward compression wave, BCW) and wave speed. Results: Comparing patients with isolated BAV and with BAV associated with repaired COA (n=25 in each group), no differences were observed in left ventricle ejection fraction, GLS or ventricular volumes, whilst significant increases in FCW and FEW magnitude were noted in the BAV and repaired COA group. The FCW inversely correlated with age and aortic size. Whilst the BCW was not significantly different comparing patients with/without COA, its magnitude tends to increase with lower coarctation index. Patients with repaired coarctation exhibit higher wave speedy velocity. Aortic wave speed (inversely related to distensibiliy) was not significantly different between the two groups. Conclusion: In the absence of a significant restenosis, VA coupling in patients with BAV and COA is not negatively affected compared to patients with isolated BAV. A reduction in the magnitude of the early systolic forward compression wave was observed in patients who were older and with larger aortic diameters.